2021
DOI: 10.2217/nmt-2021-0030
|View full text |Cite
|
Sign up to set email alerts
|

Repository Corticotropin Injection Improves Quality Metrics in an Observational Study of Multiple Sclerosis Relapse

Abstract: Aim: To determine whether clinicians evaluate American Academy of Neurology (AAN) quality metrics for patients with multiple sclerosis (MS) relapse and whether repository corticotropin injection (RCI) improves clinical and patient-reported outcomes associated with these metrics at 2 and 6 months after treatment. Methods: A multicenter, prospective, observational registry evaluating patients receiving RCI for MS relapse (N = 125) categorized data according to AAN quality metrics involving diagnosis, disability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Significant improvements were noted in MS response to CI treatment, rendering CI a plausible alternative for acute exacerbation. A year later, the same team of authors [40], assessed clinical and patientreported outcomes at 2 and 6-month period in 125 relapsing MS patients who received CIs. Improvement on many quality metrics was marked in MS patients, following CI treatment.…”
Section: Acth Nervous System and Pediatric Population Neurological In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Significant improvements were noted in MS response to CI treatment, rendering CI a plausible alternative for acute exacerbation. A year later, the same team of authors [40], assessed clinical and patientreported outcomes at 2 and 6-month period in 125 relapsing MS patients who received CIs. Improvement on many quality metrics was marked in MS patients, following CI treatment.…”
Section: Acth Nervous System and Pediatric Population Neurological In...mentioning
confidence: 99%
“…Nguyen et al [16], Sharon et al [17] and Nelson et al [18] eye uveitis Bryan et al [20] eye optic neuritis Wirta et al [21] eye keratitis Anesi et al [22] eye retinal vasculitis Cusick et al [38], Kaplan et al [39], [40], Hunter et al [41] nervous system multiple sclerosis Chugani et al [44], Knupp et al [45], O'Callaghan et al [47], Yin et al [50] pediatrics infantile spasms Gills et al [55], Fleischmann et al [57] musculoskeletal rheumatoid arthritis Furie et al [66,67], Askanase et al [68,69] musculoskeletal sle Aggarwal et al [74] musculoskeletal inflammatory myopathy Baughman et al [75], Chopra et al [76], Rahaghi et al [77] musculoskeletal sarcoidosis Daoussis et al [85], [86], Xu et al [91] musculoskeletal gout…”
Section: Diseasementioning
confidence: 99%
“…Results of an observational prospective registry study of MS relapse found that patients treated with Acthar showed significant improvements in disease assessment scores, including the MS Impact Scale Version 1, the Clinical Global Impression of Improvement, and Work Productivity and Activity Impairment Questionnaire: MS at 2- and 6-month timepoints [ 50 ]. A follow-up analysis of the registry study showed that American Academy of Neurology quality metrics guidelines were followed by health care professionals during Acthar treatment in patients with MS relapse, and Acthar was associated with improved outcomes in the domains of disability, fatigue, cognitive impairment, depression, and quality of life [ 51 ].…”
Section: Clinical Studies Of Acthar: 2014–2022mentioning
confidence: 99%